THE PLACE AND PROSPECTS OF DIGITAL PEDAGOGY IN THE MODERN EDUCATION SYSTEM - Toshpulatova (Xolmurodova) Maftuna (Western European Studies, 2025)
Digital pedagogy refers to planning, delivering, and evaluating teaching experiences that take advantage of digital technologies to support student learning. Digital pedagogy has changed in the modern education system from an add-on resource to a central instruction, assessment, and collaboration platform. This article synthesizes the current evidence concerning the effect of digital technologies—learning management systems, video conferencing, online resources, adaptive learning, data analytics, and emerging AI tools—on teaching and learning processes. It addresses benefits such as flexibility, customization, scalability, and access to numerous resources, but also challenges such as the digital divide, privacy and data security, quality control, teacher preparation, and the risk of less human centered interaction. The article reflects on the development of digital pedagogy, emphasizing blended and hybrid models, learner-centered design, and the potential of AI and immersive technologies to tailor and enable instruction and support. It concludes with policy and practice implications for ensuring equitable access, robust pedagogy, and informing future research on learning outcomes, equity, and long-term consequences of digital interventions in education.
Keywords: digital pedagogy; educational technology; online learning; digital literacy